Changes in newspaper coverage of mental illness from 2008 to 2014 in England. (August 2016) - Rhydderch, D.; Krooupa, A.‐M.; Shefer, G.; Goulden, R.; Williams, P.; Thornicroft, A.; Rose, D.; Thornicroft, G.; Henderson, C.
Abstract : Objective: This study evaluates English newspaper coverage of mental health topics between 2008 and 2014 to provide context for the concomitant improvement in public attitudes and seek evidence for changes in coverage. Method: Articles in 27 newspapers were retrieved using keyword searches on two randomly chosen days each month in 2008–2014, excluding 2012 due to restricted resources. Content analysis used a structured coding framework. Univariate logistic regression models were used to estimate the odds of each hypothesised element occurring each year compared to 2008. Results: There was a substantial increase in the number of articles covering mental health between 2008 and 2014. We found an increase in the proportion of antistigmatising articles which approached significance at P  < 0.05 (OR = 1.21, P  = 0.056). The decrease in stigmatising articles was not statistically significant (OR = 0.90, P  = 0.312). There was a significant decrease in the proportion of articles featuring the stigmatising elements 'danger to others' and 'personal responsibility', and an increase in 'hopeless victim'. There was a significant proportionate increase in articles featuring the antistigmatising elements 'injustice' and 'stigma', but a decrease in 'sympathetic portrayal of people with mental illness'. Conclusion: We found a decrease in articles promoting ideas about dangerousness or mental illness being self‐inflicted, but an increase in articles portraying people as incapable. Yet, these findings were not consistent over time.